Medicinal plants used as female contraceptives in India: a review - Sharma, Pramod Parasharam; Kature, Shilpa Kashinath; Sharma, Sakshi Pramod (International Journal of Research in Medical Sciences, 2024)
Contraception means prevention of conception. There are a variety of modern medicines and methods are existing in accordance to their nature of use. Some medicines/methods support short period birth control, while some other gives long term birth control or permanent sterility. But all modern medicines / methods have benefits as well as side effects associated with them. On other hand, plant medicines used for female contraception provide alternate way to avoid pregnancy as which show lesser side effects. Several plants have been used to prevent conception since ancient time and pharmacological researches have proved antifertility potential of several plant medicines. In present review information of different medicinal plants used as female contraceptive is provided. Information of 116 plants for preparing 130 formulations used as female contraceptives along with, plant part used, mode of preparation of medicine, mode of administration and references of the research publication from which information such as, traditional uses and pharmacological studies have been gathered.